2009
DOI: 10.1111/j.1751-553x.2008.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin plasma levels decrease is associated with preeclampsia worsening

Abstract: Antithrombin plasma levels (AT) have been found decreased in women with preeclampsia (PE), but little is known about the trend of AT during the course of this disease. We prospectively investigated AT in consecutive women admitted to our hospital with a diagnosis of PE, to assess if AT fluctuations could be associated with the evolution of the disease. AT, platelet count and D-dimer levels were determined every other day. In the 73 patients studied, AT, platelet count and fibrinogen progressively reduced durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
4
9
0
Order By: Relevance
“…Possible reasons for this have been suggested to be enhanced consumption due to intravascular coagulation activation, depressed hepatic synthesis and increased urinary loss because of the low molecular weight of AT. 9,35,36 Our study confirmed previous reports of significantly lower AT values in patients with TA B L E 3 Parameters of global haemostatic assays and fibrin clot turbidity analysed in patients with P-EC before and after delivery (n = 42) and in controls (n = 80)…”
Section: Discussionsupporting
confidence: 88%
“…Possible reasons for this have been suggested to be enhanced consumption due to intravascular coagulation activation, depressed hepatic synthesis and increased urinary loss because of the low molecular weight of AT. 9,35,36 Our study confirmed previous reports of significantly lower AT values in patients with TA B L E 3 Parameters of global haemostatic assays and fibrin clot turbidity analysed in patients with P-EC before and after delivery (n = 42) and in controls (n = 80)…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, Marietta et al . determined a correlation between the decreased plasma level of AT‐III and increased hypertensive complications of pregnancy 21 . Osmanagaoglu et al .…”
Section: Discussionmentioning
confidence: 99%
“…20 Likewise, Marietta et al determined a correlation between the decreased plasma level of AT-III and increased hypertensive complications of pregnancy. 21 Osmanagaoglu et al have also suggested that AT-III may be a useful marker in monitoring the course of the disease. 18 Hyperhomocysteinemia is associated with vascular diseases, such as hypertension, cerebrovascular accidents, peripheral vascular diseases, as well as early pregnancy loss and placental abruption.…”
Section: Discussionmentioning
confidence: 99%
“…[111][112][113][114][115][116][117] Review of 61 women with AFLP found a mean ATIII level of 16.1% (0-69%) compared with mean levels of 60-85% in PET, and 62-80% in HELLP. [118][119][120][121][122][123][124] An ATIII level of less than 65% is suggestive of the diagnosis of AFLP. [124][125][126] Fibrinogen levels rise significantly during pregnancy and the use of non-pregnant reference intervals may underestimate the prevalence of DIC.…”
Section: Measures Of Coagulopathymentioning
confidence: 99%